2014
DOI: 10.1371/journal.pone.0100201
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Regulatory Role of WNT Signaling in Potentiating FSH Action during Bovine Dominant Follicle Selection

Abstract: Follicular development occurs in wave like patterns in monotocous species such as cattle and humans and is regulated by a complex interaction of gonadotropins with local intrafollicular regulatory molecules. To further elucidate potential mechanisms controlling dominant follicle selection, granulosa cell RNA harvested from F1 (largest) and F2 (second largest) follicles isolated at predeviation (PD) and onset of diameter deviation (OD) stages of the first follicular wave was subjected to preliminary RNA transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
44
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 27 publications
11
44
2
Order By: Relevance
“…The abundance of Wnt members in growing follicles increases after human Chorionic gonadotropin administration in rodents (Hsieh, Mulders, Friis, Dharmarajan, & Richards, ). The role of WNT regulating the function of FSH on cattle follicular cells has also been described (Abedini, Zamberlam, Boerboom, & Price, ; Gupta et al, ). The importance of Wnt signaling in the ovary is demonstrated by the phenotype associated with Wnt4 ovarian conditional‐knockout mice, which exhibit a 75% reduction in antral follicles that is probably due to increased follicular atresia (Boyer, Lapointe et al, ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The abundance of Wnt members in growing follicles increases after human Chorionic gonadotropin administration in rodents (Hsieh, Mulders, Friis, Dharmarajan, & Richards, ). The role of WNT regulating the function of FSH on cattle follicular cells has also been described (Abedini, Zamberlam, Boerboom, & Price, ; Gupta et al, ). The importance of Wnt signaling in the ovary is demonstrated by the phenotype associated with Wnt4 ovarian conditional‐knockout mice, which exhibit a 75% reduction in antral follicles that is probably due to increased follicular atresia (Boyer, Lapointe et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…The abundance of Wnt members in growing follicles increases after human Chorionic gonadotropin administration in rodents (Hsieh, Mulders, Friis, Dharmarajan, & Richards, 2003). The role of WNT regulating the function of FSH on cattle follicular cells has also been described (Abedini, Zamberlam, Boerboom, & Price, 2015;Gupta et al, 2014).…”
mentioning
confidence: 99%
“…Canonical WNT signaling is governed by the interaction of β-catenin with other molecules to regulate cellular decisions related to proliferation, differentiation, and morphogenesis (Willert & Jones 2006, Komiya & Habas 2008, Angers & Moon 2009). A series of studies have identified the expression and regulation of WNT ligands and downstream WNT signaling components in the developing follicle and corpus luteum of rats, mice, humans, and cattle (Hsieh et al 2002, Ricken et al 2002, Harwood et al 2008, Wang et al 2009, Castanon et al 2012, Gupta et al 2014) (Table 1). However, characterization of specific WNT molecules during folliculogenesis has been focused primarily on Wnt2 /WNT2 and Wnt4 /WNT4 in mice, rats and humans, although recent studies have unveiled contributions of frizzled receptor agonist, WNT3A in follicular development and steroid production of mice and rats (Li et al 2014, Stapp et al 2014).…”
Section: The Role Of Wnt In Follicle Developmentmentioning
confidence: 99%
“…Follicular development is related to the transient increase of serum FSH that promotes the emergence of small follicles (Gupta et al, 2014). However, the decreasing concentration of serum FSH disrupts the development of the subordinate follicles that enter atresia and interrupts the selection of new subordinate follicles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the decreasing concentration of serum FSH disrupts the development of the subordinate follicles that enter atresia and interrupts the selection of new subordinate follicles. A single follicle continues development (growth) to ovulatory size with an increase in the amount of estradiol synthesis, since the subordinate follicles lose the ability to synthesize estradiol and die from follicular atresia (Adams et al, 2008;Gupta et al, 2014;Nasser et al, 1993).…”
Section: Introductionmentioning
confidence: 99%